Metabolic syndrome in overweight and obese adolescents - Pajuelo, Jaime (2007)
Objective: To determine the presence of metabolic syndrome in overweight and obese adolescent population. Design: Clinical study. Setting: Endocrinology service. Hospital Nacional Dos de Mayo. Participants: Adolescents. Interventions: We studied 195 adolescents between 10 to 19 year-old. Inclusion criteria was that they should be overweight or obese. We used the reference population of Must et al. with the following diagnosis criteria: 85 to 95 percentile, overweight; higher than 95 percentile, obese. Weight, height and waist circumference (WC) were taken following international recommendations. Metabolic syndrome determination followed Cook recommendations (TG > 110, cholesterol HDL < 40 mg/dL, glycemia > 110 mg/dL y WC > 90 percentile), the presence of three or more of these criteria indicated metabolic syndrome. Main outcome measures: Setabolic syndrome, overweight, obesity. Results: Metabolic syndrome was present in 8,8% of the studied population. Those with obesity presented a higher prevalence of metabolic syndrome than those overweight (22,9 and 3%, respectively). It occurred more in the male gender (24,1%) than in the female (2,9%) and in those 15 year-old and over, 9,7% compared with the other younger group, 7,4%. As WC increased, metabolic syndrome also increased. Conclusions: Metabolic syndrome is present in the adolescent population, although with low prevalence, but intimately related to nutritional status (overweight and obesity). Tendency of these nutritional alterations is to increase and as a consequence more and more adolescents will have metabolic syndrome that implies health risk.